Extent of Lopping in Relation to Acorn Production of Quercus floribunda Lindle Forests - Rana, Isha; Singh, V. R. R.; Singh, Ombir (Indian Forester, 2015)
Quercus floribunda (Moru oak) (Local name Tilonj) is an important element of western and central Himalayan vegetation. Lopping practice is very common in the forests and plantations especially near the habitation. Q. floribunda tree is lopped for fodder, which is the most appreciated among all oaks. However, heavy and indiscriminate lopping continues throughout the year which results pole like appearance of the trees with scanty leaves. Lopping of Q. floribunda results in poor production of acorns. The study suggests that there is need to understand the effect of lopping on acorn production to have sustainable lopping levels.